Antimicrobial photodynamic inactivation: a bright new technique to kill resistant microbes - Hamblin, Michael R (Curr Opin Microbiol, 2016)
Photodynamic therapy (PDT) uses photosensitizers (non-toxic dyes) that are activated by absorption of visible light to form reactive oxygen species (including singlet oxygen) that can oxidize biomolecules and destroy cells. Antimicrobial photodynamic inactivation (aPDI) can treat localized infections. aPDI neither causes any resistance to develop in microbes, nor is affected by existing drug resistance status. We discuss some recent developments in aPDI. New photosensitizers including polycationic conjugates, stable synthetic bacteriochlorins and functionalized fullerenes are described. The microbial killing by aPDI can be synergistically potentiated (several logs) by harmless inorganic salts via photochemistry. Genetically engineered bioluminescent microbial cells allow PDT to treat infections in animal models. Photoantimicrobials have a promising future in the face of the unrelenting increase in antibiotic resistance.